Tradition lubuk larangan as a local wisdom for ecocultural tourism river management through landscape anthropolinguistic approach in Mandailingnese. Issue 1 (November 2021) - Lubis, T; Dardanila; Nasution, T; Zulkarnain; Hasrul, S; Ramlan; Abus, A F
Abstract: Lubuk larangan is a pond that contains freshwater fishes in Kecamatan Tambangan, Kabupaten Mandailing Natal, North Sumatera. The objective of this study was to describe eco cultural tourism river management at the core of the landscape anthropolinguistic approach. The method was qualitative, and an interactive model was implemented. The data were collected by doing an interview and participant observation. Then they were analyzed data reduction, data display, and verifying/conclusion with landscape anthropolinguistic as an approach. This approach was the new paradigm to describe and explain the analysis from a linguistic perspective in landscape study. The study results showed that Lubuk larangan was a natural resource for the villagers economically and contained social, cultural ecology, and religious value. It became a tradition and belonged to Mandailingnese as their local wisdom. It can be concluded that Lubuk larangan became a concept for them to understand and apply management for maintaining environmental usage patterns with cultural-based tourism space.